Alcohol use and misuse, self-harm and subsequent mortality: an epidemiological and longitudinal study from the multicentre study of self-harm in England. Issue 10 (6th January 2015) - Ness, Jennifer; Hawton, Keith; Bergen, Helen; Cooper, Jayne; Steeg, Sarah; Kapur, Navneet; Clarke, Martin; Waters, Keith
Abstract : Objectives: Alcohol use and misuse are strongly associated with self-harm and increased risk of future self-harm and suicide. The UK general population prevalence of alcohol use, misuse and alcohol-attributable harm has been rising. We have investigated the prevalence of and trends in alcohol use and misuse in self-harm patients and their associations with repeat self-harm and subsequent death. Methods: We used patient data from the Multicentre Study of Self-Harm in England for 2000–2009 and UK mortality data for patients presenting from 2000 to 2007 who were followed up to the end of 2009. Results: Alcohol involvement in acts of self-harm (58.4%) and alcohol misuse (36.1%) were somewhat higher than found previously in self-harm patients. Alcohol involvement and misuse were most frequent in men, those aged 35–54 years and those from white ethnicities. The frequency of alcohol misuse increased between 2000 and 2009, especially in women. Repetition of self-harm was associated with alcohol involvement in self-harm and particularly with alcohol misuse. Risk of suicide was increased significantly in women misusing alcohol. Conclusions: Alcohol use and misuse in self-harm patients appears to have increased in recent years, particularly in women. The association of alcohol with greater risk of self-harm repetition and mortality highlights the need for clinicians to investigate alcohol use in self-harm patients. Ready availability of alcohol treatment staff in general hospitals could facilitate appropriate aftercare and the prevention of adverse outcomes.